ISLAM BAYAN: AN ANALYSIS OF RELIGIOUS BEHAVIOR ON GAMA AND LUIR GAMA TRADITIONAL CEREMONIES IN LOMBOK NTB - Muhammad Ahyar (International Journal of Social Science, 2023)
This study examined adherents of Islam Bayan or Islam Wetu Telu at the Gama and Luir Gama traditional ceremonies in Lombok, West Nusa Tenggara. This research uses qualitative methods to understand the religious behaviour of Islam Wetu Telu at Gama and Luir Gama traditional ceremonies. The theories used in this study are social action theory and functional structural theory. The findings of this study reveal that Gama traditional ceremonies consist of various behaviour related to religious celebrations. Meanwhile, the Luir Gama traditional ceremony, which is a ceremonial activity held in connection with the occurrence of a long drought and excessive rainfall. This ceremony is carried out once a year, precisely in the first year of the sewindu, namely the year of Alip. Luir Gama customs can be divided into two types of ceremonies, namely Taik Lauk and Taik Daye. The Taik Lauk ritual is held when facing the changing drought, while the Taik Daye ritual is held when entering the rainy season every year. The main actors, all religious ceremonies are traditional leaders and Kiai Kagungan which the author calls central behaviour. The factors behind the religious behaviour of Islam Wetu Telu in Gama and Luir Gama traditional ceremonies are internal and external factors. Internal factors are related to changes in the attitudes of traditional leaders, willingness to acculturate, and the ability to perform adaptation. Meanwhile, external factors concern the history of the entry of Islam in Lombok, Islamic Da'wah, and Hinduization